2002
DOI: 10.1124/jpet.300.2.408
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Protection of Synaptic Function, Spatial Learning, and Memory from Transient Hypoxia in Rats

Abstract: Hypoxia significantly reduced cholinergic activity in rat CA1 field and intracellular in the CA1 pyramidal cells, recorded in hippocampal slices. The hypoxic responses of the hippocampal CA1 pyramidal cells to a brief hypoxia consisted of a short period of "synaptic arrest", observed as an elimination of excitatory postsynaptic current under voltage clamp and recovered immediately as oxygenation was reinitiated. The hypoxic synaptic arrest was not associated with reduced postsynaptic responses of the pyramidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…This raises the question how miR-210, which has previously been associated with hypoxia response 24 , may affect memory. Considering the extreme sensitivity of neural structures and neurons to hypoxia 57 , we suggest small changes to oxygen levels in metabolic activity neurons may induce expression of miR-210, which in turn targets key molecules including asparagine synthetase and actin.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question how miR-210, which has previously been associated with hypoxia response 24 , may affect memory. Considering the extreme sensitivity of neural structures and neurons to hypoxia 57 , we suggest small changes to oxygen levels in metabolic activity neurons may induce expression of miR-210, which in turn targets key molecules including asparagine synthetase and actin.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the stimulatory effect elicited by certain position 8 variants at NR2A-containing receptors may reflect their preferential, or sole, occupancy of the putative stimulatory site. Binding to this sight may stabilize the interdimer interface of the NMDAactivated receptor, obviating the desensitization that arises from reorientation of the agonistbound interface (Sun et al, 2002).…”
Section: [M8a] and Con-t[m8q]) Or Partially (Con-t[m8e] Con-t[m8i]mentioning
confidence: 99%
“…Moreover, they found long-lasting posthypoxic impaired learning and memory in rats according to a water maze test, without evidence of cellular damage on histological examination, consistent with a transmission defect without structural neuronal damage. 43 Bolay et al 41 found a restored axonal conduction, but a lasting impairment of cortical synaptic transmission by means of intracortically evoked potentials in the rat motorcortex after transient focal ischemia in vivo. In a later study, they showed a long-lasting defect of synaptic transmission in the penumbral region after transient middle cerebral artery occlusion in rats.…”
Section: Evidence Of Presynaptic Failurementioning
confidence: 99%
“…8,35,36 Thereafter, changes in synaptic responses after variable periods of hypoxia or ischemia have been shown frequently in vitro 37,38,39,40 and in vivo, 41,42,43 and several causes of presynaptic and postsynaptic ischemic failure have been postulated.…”
Section: Synaptic Failure In Ischemiamentioning
confidence: 99%
See 1 more Smart Citation